PENGARUH PRICE EARNING RATIO, PRICE TO BOOK VALUE, DAN INFLASI TERHADAP HARGA SAHAM YANG TERINDEKS IDX 30 - Niki Nony Mutiarani; Riana R Dewi; Suhendro Suhendro (ITB AAS INDONESIA Surakarta, 2019)
This study aims to determine how the effect of Price Earning Ratio, Price to Book Value Ratio and Inflation on Indexed Stock Prices Idx 30 in the period 2016-2018. The object in the 2016-2018 research period was a company whose share price was IDX30 Teindeks on the Indonesia Stock Exchange. The population used in this study is 30 company shares and is based on a purposive sampling method that produces a sample of 11 companies. The dependent variable is represented by the stock price index, while the independent variables in this study are Price Earning Ratio, Price to Book Value Ratio and inflation. The research method used is a quantitative method that takes into account the company's market ratios of financial reports obtained from the IDX website and the level of inflation in Indonesia Partially the results of this study indicate that during the 2016-2018 period Price Earning Ratio, Price to Book Value Ratio and inflation do not affect IDX indexed stock prices 30. Keywords: Stock Prices, Price Earning Ratio, Price To Book Value, Inflation